Sociolinguística com foco na comunidade LGBTQIA+: atitude, identidade e estigma - Souza-Silva, André Luiz (2022)
Linguistics studies have distinct analytical exponents, and among them, the Sociolinguistics studies work in different domains of the indissociable relationship between language and society. Furthermore, this dissertation departs from Sociolinguistics concepts of the variationist third wave bias, Queer Studies (BORBA, 2020), and Feminist (LOURO, 2019). These studies contribute to consolidating and developing Linguistic studies, especially the attitude studies that focus on more restrict groups. That said, our objective is to analyze sociolinguistic attitudes of LGBTQIA+ and Cis/Hetero regarding the community language and speakers. To do that, we have adopted as theoretical framework Labov (2008[1972]), Preti (1977, 1984, 2010), Bagno (2007, 2012, 2017), Bortoni-Ricardo (2004, 2011 [1985], 2017), Freitag (2015), Veloso (2014), among other, aligning this work within a non exclusively theoric based Sociolinguistics. Moreover, we revindicate an activist posture that promotes a Linguistic Attitudes approach that considers the contribution of Lambert & Lambert (1972), Milroy (2011 [2001]), Hora (2011), Cardoso (2015), among other voices. Thus, this study mobilizes, predominantly, a qualitative and phenomenological nature (MERLEAU-PONTY, 1999) based on a questionnaire and a semi-structured interview. These instruments enable the data generation among the 20 (twenty) participants divided into two groups: the diversity group - 10 LGBTQIA+, and the heteronormative group - 10 Cis/Heteros. In this methodological path, we obtained data indicating that some LGBTQIA+ speakers recognize, as usual, linguistics items involving common marked variations, specifically in their community. They also operate phenomenons of the particularly pragmatic context, such as linguistic uses more distant from the Cis/Hetero group. Besides that, Cis/Hetero participants do not bend to more negative constructions of the psychosocial profile of LBGTQIA+ speakers. Thus, the evaluation of LGBTQIA+ speakers' profiles is proportionally similar in both groups. However, as a symbol of social activism and social fight, some LGBTQIA+ participants seem to defend the group's language by recognizing the importance of the sociolect as part of the performative and shifting identity.